2011
DOI: 10.1007/s10549-011-1758-x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α directly regulates sensitivity to paclitaxel in neoadjuvant chemotherapy for breast cancer

Abstract: Neoadjuvant chemotherapy (NAC) has become the standard treatment for advanced breast cancer. Several prognostic markers, including estrogen receptor-α (ERα), are used to predict the response to NAC. However, the molecular significance of ERα expression in the efficacy of chemotherapy is not yet fully understood. To examine this issue, we first evaluated ERα transcriptional activity in breast cancer cells derived from pre-NAC specimens using estrogen response element-green fluorescent protein (ERE-GFP) as a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…We clearly observed that silencing the ERa in ERa positive breast cancer cells negated hyperglycaemia-induced chemoresistance; consistent with these findings we determined that exposing ERa negative breast cancer cells to different levels of glucose did not influence chemo-sensitivity. The ERa has been linked to chemoresistance previously: Tokuda et al (2012) showed that silencing the ERa in MCF7 breast cancer cells enhanced sensitivity to paclitaxel. This study was only performed under hyperglycaemic conditions and in that context their results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…We clearly observed that silencing the ERa in ERa positive breast cancer cells negated hyperglycaemia-induced chemoresistance; consistent with these findings we determined that exposing ERa negative breast cancer cells to different levels of glucose did not influence chemo-sensitivity. The ERa has been linked to chemoresistance previously: Tokuda et al (2012) showed that silencing the ERa in MCF7 breast cancer cells enhanced sensitivity to paclitaxel. This study was only performed under hyperglycaemic conditions and in that context their results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…27 Other researchers have demonstrated that high ER expression affected estrogen-regulated genes and enhanced cell motility, which was associated with resistance to paclitaxel therapy. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapies and radiation therapy induce DNA damage, so ERα may suppress the DDR to reduce the efficacy of these treatments. Indeed, patients with ER positive breast cancers have significantly lower response rates to chemotherapy than those with ER negative cancers (88), and in vitro studies suggest this is dependent on ERα action (8991). Co-administration of anti-estrogens and radiation therapy or chemotherapy appears to enhance therapy cytotoxicity and a likely explanation is that anti-estrogen treatment prevents pro-proliferative bypass of cytotoxicity by estrogen (66, 90).…”
Section: Perspectivesmentioning
confidence: 99%